Jealousy Is Influenced by Sex of the Individual, Their Partner, and Their Rival - Fernandez-Tapia, A (SPRINGER/PLENUM PUBLISHERS, 2022)
Jealousy is an affective state activated by a perceived threat to a valued relationship by a third party. On average, males report higher distress about their partner s sexual extra-pair involvement, while females show higher emotional jealousy. These sex differences are specific to heterosexuals and to contexts with potential reproductive costs. We tested the effect of sex and sexual orientation of the individual, and sex of the partner and potential rival on sexual versus emotional jealousy. Sexual orientation was operationalized as a willingness to form long-term relationships with men, women, or both. Heterosexual, homosexual, and bisexual males (N = 416) and females (N = 1328) from Brazil, Chile, and Portugal responded to the Sexual vs. Emotional Jealousy Scale and then ranked their distress to four hypothetical scenarios: sexual or emotional involvement of their partner with a male or a female rival. This is the first study to simultaneously test for an effect of self, partner, and rival sex on jealousy: bisexual individuals responded twice, about a hypothetical female and about a male partner. Individuals were most preoccupied with their partner s emotional relationship with a rival of the same sex as the respondent. Heterosexual males reported higher sexual jealousy than the other groups, but did not differ from bisexual men responding about female partners. Bisexual females were more upset by sexual extra-pair involvement of their female (versus male) partners with a male rival. Thus, jealousy was influenced by sex and sexual orientation of the individuals, sex of the partners, and also by sex of the rivals: same-sex rivals were perceived as most threatening. This suggests that besides being a strategy to maintain a primary relationship, jealousy is particularly sensitive to same-sex competitors, being an intra-sexual competition strategy.